Necesidad de reformar artículos del código de la niñez y adolescencia respecto al apremio personal del alimentante y los obligados subsidiarios por cuanto causan la colisión de derechos garantizados en la Constitución del Ecuador, como el derecho a la libertad y el derecho de las niñas, niños y adolescentes - Figueroa Saavedra, Cielito Heinert (2015)
The Constitution of the Republic of Ecuador, is clear as to determine the binding between the state, society and family, to protect the rights and interests of children and adolescents, protected by the principles of primacy and interests the rights of this vulnerable group, hence the Organic Code on Children and Adolescents has collected in terms similar to those afforded by the Constitution. With the emergence of the Code for Children and Adolescents in 2003, the scope of protection is much more advanced and guaranteeing comprehensive protection that the State should provide children and adolescents, as well as ensuring the compliance with the rights enshrined in the Constitution, which has been given to the right to food as a fundamental right. Hence the Legislative Branch, through the assembly in order to protect children has been introduced in the Code of Childhood and Adolescence some legal reforms in relation to food regimen, same that are important to forewarn welfare children and adolescents, hence it has established itself as a coercive measure staff urge those who do not fulfill their obligation to pay their alimony. While the measures included in the Code for Children and Adolescents such as the Personal or urged the obligor and the staff urged the subsidiary required can partly solve the problem through imprisonment forcing the person the immediate payment of maintenance, but the fact remains that the privacy of freedom can lead to much more serious such as family breakdown, job loss problems, these situations that prevent the economic returns obligor for payment and maintenance of his family. Starting from these regulations, the State as such must be the generator of employment, situation that is far away and that, based on data generated by the National Institute of Statistics and Censuses, INEC, 2014 to September there is a 44.57% of employment; 51.20% from 3.90% underemployment and unemployment. This report also states that approximately 8 of every 10 jobs in urban areas are generated by the private sector, a figure that confirms that the State fails to comply with Article 33 of the Constitution by not creating the jobs needed and thus avoid problems legal to restrict freedom of the people as is the case when the obligor or violate subsidiary required to pay two or more child support staff are of urgency based on the provisions of the Code of Childhood and Adolescence. These circumstances have led to execute this research study whose primary objective is to raise proposed amendment to Articles 22 and 23 unnumbered the Code of Children and Adolescents, to do a doctrinal legal analysis was conducted urgency staff, as injuries damaging cohesion and implemented in the Code for Children and Adolescents in order to compel the obligor to pay alimony and develop alternatives that will help solve the problem keeping the family as the fundamental unit of society. This research has its foundation in the Constitution of the Republic of Ecuador, the legal instruments that are based Human Rights and of the Child, the Civil Code, the Organic Code on Children and Adolescents and other related standards